Awareness and attitude towards human papillomavirus and its vaccine among females with and without daughter(s) who participated in cervical cancer screening in Shenzhen, China. Issue 9 (24th July 2019) - Lin, Wei; Wang, Yueyun; Liu, Zhihua; Chen, Bin; Yuan, Shixin; Wu, Bo; Gong, Lin
Abstract: Objectives: To evaluate the awareness of HPV and HPV vaccine, and willingness to be vaccinated against HPV, among women with and without daughter(s) in Shenzhen, China. Methods: Cross‐sectional survey in January and June 2015 by means of a self‐administered questionnaire to collect information. Multivariate logistic regression was used to explore the factors associated with awareness of HPV and its vaccine and the willingness to be vaccinated. Results: A total of 9855 women (mean age 37.09 years, SD 7.48) were included in the analysis. Although only 42.3% had heard of HPV and 21.0% of HPV vaccine, 63.3% were willing to be vaccinated. 73.9% of the 5799 women with daughter(s) were willing have their daughter(s) vaccinated. Women with daughter(s) did not have a higher awareness of HPV (43.2% vs . 41.5%, P  =   0.109) and HPV vaccine (21.1% vs . 20.9%, P  =   0.854) than women without daughter(s), but did tend to be more willing to be vaccinated themselves (66.3% vs . 59.9%, P  < 0.001). Women's awareness of HPV and specific knowledge of HPV vaccine were predictors of the willingness to have both themselves and their daughters vaccinated. These associations may be modified by residency status, education and monthly income. Conclusions: Although awareness of HPV and HPV vaccine among women in Shenzhen was low, willingness to have themselves and their daughter(s) vaccinated was relatively high, especially among mothers. High awareness of HPV and its vaccine will help improve the acceptability of HPV vaccination according to residency status, education and monthly income. Abstract : Objectifs: Evaluer la connaissance sur le VPH et du vaccin contre le VPH et la volonté de se faire vacciner contre le VPH chez les femmes avec et sans fille(s) à Shenzhen, en Chine. Méthodes: Enquête transversale menée en janvier et juin 2015 au moyen d'un questionnaire auto‐administré destiné à recueillir des informations. La régression logistique multivariée a été utilisée pour explorer les facteurs associés à la connaissance sur le VPH et sur son vaccin et à la volonté de se faire vacciner. Résultats: 9.855 femmes (âge moyen: 37, 09 ans, écart‐type: 7, 48) ont été incluses dans l'analyse. Bien que seulement 42, 3% aient entendu parler du VPH et 21, 0% du vaccin contre le VPH, 63, 3% étaient prêtes à se faire vacciner. 73, 9% des 5.799 femmes avec des filles ont bien voulu se faire vacciner. Les femmes avec des filles ne connaissaient pas mieux le VPH (43, 2% contre 41, 5%, P = 0, 109) et le vaccin contre le VPH (21, 1% contre 20, 9%, P = 0, 854) que celles sans fille(s), mais avaient tendance à être plus disposées à être vaccinées (66, 3% contre 59, 9%, P <0, 001). La sensibilisation des femmes au VPH et leur connaissance spécifique sur le vaccin contre le VPH étaient des facteurs prédictifs de la volonté de se faire vacciner, elles et leurs filles. Ces associations pourraient être modifiées en fonction du statut de résidence, de l'éducation et du revenu mensuel. Conclusions: Bien que les femmes à Shenzhen aient été peu sensibilisées au VPH et au vaccin contre le VPH, la volonté de se faire vacciner et de faire vacciner leurs filles était relativement élevée, en particulier chez les mères. Une connaissance élevée sur le VPH et sur son vaccin contribuera à améliorer l'acceptabilité de la vaccination contre le VPH indépendamment du statut de résidence, de l'éducation et du revenu mensuel.